2011
DOI: 10.1080/10420150.2011.570008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SHI irradiation on the critical current density of Y1−xCaxBa2Cu3O7−δthick film with Y2O3composite

Abstract: Y 1−x Ca x Ba 2 Cu 3 O 7−δ (x = 0.1) + Y 2 O 3 (10 wt%) composite thick film has been prepared by the diffusion reaction technique. Samples are irradiated with 200 MeV Ag ions. X-ray diffraction and scanning electron microscopy reveal microstructural changes in the irradiated samples. The enhancement of the critical current density (J c ) from 1.4 × 10 4 to 6.7 × 10 4 A/cm 2 with irradiation in YCaBCO samples is observed, indicating that flux pinning increases due to the creation of columnar defects induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In order to tailor the superconducting properties we have used 5 wt.% and 10 wt.% of Y 2 O 3 in YBCO matrix and irradiated it with 200 MeV of Ag ions. In our previous published works on thick films [24,25] we have added 10 wt.% Y 2 O 3 to YBCO and Y 1Àx Ca x BCO matrix, irradiated it with 200 MeV Ag ions. A comparative study for magnetization measurement was reported for pristine YBCO and YBCO/10 wt.% Y 2 O 3 thick films with and without irradiation [24].…”
Section: Introductionmentioning
confidence: 99%
“…In order to tailor the superconducting properties we have used 5 wt.% and 10 wt.% of Y 2 O 3 in YBCO matrix and irradiated it with 200 MeV of Ag ions. In our previous published works on thick films [24,25] we have added 10 wt.% Y 2 O 3 to YBCO and Y 1Àx Ca x BCO matrix, irradiated it with 200 MeV Ag ions. A comparative study for magnetization measurement was reported for pristine YBCO and YBCO/10 wt.% Y 2 O 3 thick films with and without irradiation [24].…”
Section: Introductionmentioning
confidence: 99%